GEOTECHNOLOGIES IN APPLIED GEOGRAPHY: DIFFUSION AND ACCESSIBILITY - Florenzano, Teresa Gallotti (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
The objective of this paper is to emphasize the diffusion of remote sensing and GIS techniques and their application to Geography. INPE (National Institute for Space Research) has participated in the development of not only sensor systems and satellite, but also  in integrated remote sensing and GIS software. Taking this into account, the focus of this presentation is on recent developments at this institution. There is also a strong emphasis on the availability of free images and software for all interested users.